1999
DOI: 10.1046/j.1460-9568.1999.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression in mammalian cells and electrophysiological characterization of two mutant Kv1.1 channels causing episodic ataxia type 1 (EA‐1)

Abstract: Episodic ataxia type 1 (EA-1) is a rare neurological disorder and was the first ionic channel disease to be associated with defects in a potassium channel. Until now 10 different point mutations in the KCNA1-gene have been reported to cause this disorder. We have investigated the functional consequences of two mutations leading to amino acid substitutions in the first and sixth transmembrane segments of a Kv1.1 channel subunit, by means of the patch-clamp technique; we injected cRNA coding for, respectively, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Functional expression in Xenopus oocytes or mammalian cells resulted in a reduction of the K currents either by diminished expression or shifts in voltage-dependence. According to these studies, both dominant negative effects on WT channels and haploinsuf®ciency can cause EA-1 [Adelman et al, 1995;Zerr et al, 1998;Bretschneider et al, 1999;Zuberi et al, 1999;Eunson et al, 2000]. A speci®c defect for those mutations going along with an epilepsy phenotype could not be found [Zuberi et al, 1999;Eunson et al, 2000].…”
Section: Episodic Ataxia Type 1 With Myokymia (And Partial Epilepsy)mentioning
confidence: 99%
“…Functional expression in Xenopus oocytes or mammalian cells resulted in a reduction of the K currents either by diminished expression or shifts in voltage-dependence. According to these studies, both dominant negative effects on WT channels and haploinsuf®ciency can cause EA-1 [Adelman et al, 1995;Zerr et al, 1998;Bretschneider et al, 1999;Zuberi et al, 1999;Eunson et al, 2000]. A speci®c defect for those mutations going along with an epilepsy phenotype could not be found [Zuberi et al, 1999;Eunson et al, 2000].…”
Section: Episodic Ataxia Type 1 With Myokymia (And Partial Epilepsy)mentioning
confidence: 99%
“…Kv1.1-containing channels exhibit variable kinetics depending on the other pore-forming subunits and associated cytoplasmic  subunits (Rettig et al, 1994;Lai and Jan, 2006). The functional consequences of KCNA1 mutations have been examined by expression of mutant and/or wild-type (WT) Kv1.1 in non-neuronal cells (Adelman et al, 1995;D' Adamo et al, 1998;Zerr et al, 1998a;Zerr et al, 1998b;Zuberi et al, 1999;Eunson et al, 2000;Bretschneider et al, 1999;Boland et al, 1999;Rea et al, 2002) . Mutations confer a loss of Kv1.1 function through altered kinetics or reduced current density, in some cases with impaired trafficking (Rea et al, 2002;Manganas et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic linkage studies in EA-1 patients have identified at least 14 mutations in the mammalian KCNA1 gene, which encodes the Kv1.1 ␣-subunit, as the underlying cause of EA-1 (2)(3)(4). Most of the KCNA1 mutations in EA-1 patients lead to Kv1.1 channels with altered biophysical characteristics, although certain mutations eliminate any detectable channel activity (5)(6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%